Biting Rates and Onchocerca Infectivity Status of Black Flies from the Simulium damnosum Complex (Diptera: Simuliidae) in Osun State, Nigeria. Issue 3 (4th January 2020) - Oforka, Linda C; Adeleke, Monsuru A; Anikwe, Joseph C; Hardy, Nate B; Mathias, Derrick K; Makanjuola, Winifred A; Fadamiro, Henry Y
Abstract: The Simulium damnosum Theobald complex transmits Onchocerca volvulus Leuckart (Spirurida: Onchocercidae), the causative agent of onchocerciasis. Recent evidence suggests that control efforts have strongly suppressed parasite populations, but vector surveillance is needed in parts of Africa where the disease remains endemic. Here, studies on biting rates and infectivity status of suspected vector species were conducted in three onchocerciasis-endemic areas, namely Iwo, Ede, and Obokun, in Osun State, Nigeria. A total of 3, 035 black flies were collected between October 2014 and September 2016, and examined for parity and parasites using standard methods. A separate collection of 2, 000 black flies was pool-screened for infectivity using polymerase chain reaction (PCR) amplification of the O-150 marker. Results showed that parous flies were significantly less common than nulliparous flies with overall parous rates of 8.02% in Iwo and 35.38% in Ede at the end of the study period. Obokun had a parous rate of 22.22% obtained in the first year only. None of the dissected parous flies were infected with O. volvulus and PCR assays showed no amplification of O-150 O. volvulus -specific repeats in head and body pools. However, annual biting rates exceeded the World Health Organization threshold of 1, 000 bites/person/yr. Thus it appears that, with such high rates of biting, even low levels of vector infection can sustain onchocerciasis in African communities.